Sea Ice Microbiota in the Antarctic Peninsula Modulates Cloud-Relevant Sea Spray Aerosol Production - Dall’Osto, Manuel; Vaqué, Dolors; Sotomayor-Garcia, Ana; Cabrera-Brufau, Miguel; Estrada, Marta; Buchaca, Teresa; Soler, Montserrat; Nunes, Sdena; Zeppenfeld, Sebastian; van Pinxteren, Manuela; Herrmann, Hartmut; Wex, Heike; et al. (Frontiers in Marine Science, 2022)
Sea spray aerosol (SSA) formation plays a major role in the climate system. The Antarctic Peninsula (AP) is affected by the greatest warming occurring in the Southern Ocean; changes in cryospheric and biological processes are being observed. Whilst there is some evidence that organic material produced by ice algae and/or phytoplankton in the high Arctic contributes to SSA, less is known about Antarctic Sea ice (sympagic) regions. To gain insight into the influence of Antarctic Sea ice biology and biogeochemistry on atmospheric aerosol, we report simultaneous water-air measurements made by means of in situ aerosol chamber experiments. For the first time, we present a methodology showing that the controlled plunging jet aerosol chamber settings do not cause major cell disruption on the studied sea ice ecosystems. Larger sea ice phytoplankton cells (>20 µm; mainly diatoms) tend to sediment at the bottom of the chamber (during the 24h experiment) and likely have a minor role on SSA production. When comparing four chamber experiments - we find that the two producing more SSA are the ones with highest abundance of nanophytoplankton cells (<20 µm; mainly nanoflagellates) as well as viruses. Our marine biogeochemical data show two broad groups of dissolved organic carbon: one rich in carbohydrates and proteic material and one rich in humic-like substances; the latter enhancing SSA production. This work provides unique insights into sea ice productivity that modulates SSA production, with potentially significant climate impacts. Further studies of these types are advised in order to see how microbiology impacts the biogeochemical cycling of elements and how aerosols are formed and processed in cold regions.